Rinosinusitis frontal lateral oculta de rara presentación con signos de fístula palpebral, ectropión y lagoftalmos. Un informe de caso - Vergara-de la Rosa, Esteban (2019)
Abstract We report an unusual case of a 53-year-old male with fistula, ectropion and lagophthalmos due to lateral frontal rhinosinusitis. Two years ago, he presented soft erythematous swelling at internal epicanthus. A year and a half before, he presented upper eyelid fistula secretion drainage, cicatricial ectropion and lagophthalmos. No otorhinolaryngological or visual discomfort was reported. Ophthalmology performed ectropion surgical repair using skin grafting, with no improvement. They requested magnetic resonance imaging which showed a suggestive image of frontal lateral sinusitis, being transferred to the Otorhinolaryngology service. External and endoscopic nasal surgery was performed, which resolved the sinus pathology with good evolution.